Enhancing intelligent connected vehicle technology instruction through flipped classroom pedagogy: A qualitative inquiry - Dan Han; Marilou Saong (International Journal of Educational Management and Development Studies, 2025)
This study explores the implementation of the flipped classroom model in teaching the intelligent connected vehicle (ICV) technology course and investigates its effect on student engagement, learning effectiveness, instructional strategies, and curriculum innovation. A qualitative descriptive research design was adopted, involving in-depth interviews with five experienced teachers and ten students from the Shaanxi Polytechnic Institute’s Automotive Intelligence program. Participants were selected through purposive sampling based on defined eligibility criteria. Semi-structured interviews focused on experiences, perceptions, challenges, and instructional practices within the flipped classroom setting. Thematic analysis was conducted to identify recurring themes and patterns in the data. Results reveal that flipped classrooms significantly enhanced student motivation, classroom interaction, and understanding of complex ICV concepts. Critical success factors included students’ prior knowledge, availability of technological resources, level of self-discipline, and the adaptability of teaching strategies. Teachers emphasized the importance of continuous student feedback in refining instructional content and delivery. Based on the findings, a structured "dual-subject, three-stage" teaching path was developed to promote personalized and active learning. However, challenges such as limited technical infrastructure and the learning difficulties of students with low self-regulation were also highlighted. Findings are limited to a single institution and specific course context, which may affect generalizability. Future research could incorporate quantitative or mixed-methods approaches and examine broader applications across various disciplines and educational settings. Nonetheless, the study offers meaningful insights into effective pedagogical strategies for teaching emerging technologies using the flipped classroom model.